2017
DOI: 10.1098/rsob.160258
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ/Activin signalling is required for ribosome biogenesis and cell growth inDrosophilasalivary glands

Abstract: Signalling by TGFβ superfamily factors plays an important role in tissue growth and cell proliferation. In Drosophila, the activity of the TGFβ/Activin signalling branch has been linked to the regulation of cell growth and proliferation, but the cellular and molecular basis for these functions are not fully understood. In this study, we show that both the RII receptor Punt (Put) and the R-Smad Smad2 are strongly required for cell and tissue growth. Knocking down the expression of Put or Smad2 in salivary gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
(78 reference statements)
2
17
0
Order By: Relevance
“…Eye-targeted knockdown of the type-II receptor punt using ey-Gal4 driven expression of UAS- punt RNAi causes absence or very strong reduction of adult retinal tissue in the majority of animals (Figure 1; (Marinho et al, 2013; Martins et al, 2017). Additionally, 42% of ey> punt RNAi animals die during pupal stage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eye-targeted knockdown of the type-II receptor punt using ey-Gal4 driven expression of UAS- punt RNAi causes absence or very strong reduction of adult retinal tissue in the majority of animals (Figure 1; (Marinho et al, 2013; Martins et al, 2017). Additionally, 42% of ey> punt RNAi animals die during pupal stage.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that rescue of punt RNAi eye phenotype by ago RNAi indeed correlated with increased Myc protein expression (Figure S4). Next, we tested the hypothesis that knockdown of ago rescues Dpp BMP2-4 signaling through the detected Myc upregulation, given the previously described genetic interaction between overexpression of Myc and Punt in eye growth and differentiation (Martins et al, 2017). Indeed that was the case, as overexpression of Myc was also sufficient for a partial rescue of differentiation in all the eye discs and adults that we observed (Figure 3B, 3F, 3I).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, through a retina-targeted double RNA interference (RNAi) screen, we identified a genetic interaction between viriato and several Drosophila transforming growth factor ␤ (TGF-␤) signaling gene members (22). This led us to study and implicate TGF-␤/activin signaling in the regulation of nucleolar biogenesis and cell growth in Drosophila salivary glands (23). Furthermore, we also disclosed that, during retina development, viriato knockdown induced an increase of p53-independent, caspase-mediated apoptotic cell death (16).…”
mentioning
confidence: 99%